Pelos caminhos do Opará: a importância do rio São Francisco para a luta dos Pankararu no Sertão de Pernambuco - Beatriz Barbosa da Silva; Claudio Ubiratan Gonçalves (Confins)
In the history of the indigenous peoples of the Northeast, Opará, a name given by the indigenous people to the São Francisco River which means “river-sea”, appears as a means of communication and also of escape, a network that interconnects the diverse peoples of the region, enabling the contact and the exchange of knowledge. In this sense, from the fieldwork experience in the lands of the Pankararu (PE), Xokó (SE) and Kariri-Xokó (AL), this article aims to understand the importance of the São Francisco River in the history and defense of the aboriginal territories located on its banks. Based on that, attention is focused on the struggle carried out by the Pankararu, who represent one of the diverse indigenous peoples that were territorialized in the Sertão do São Francisco and that started a process of self-demarcation of the territory located on the banks of the river.